Bleeding risk scales in patients with acute coronary syndrome: place of the ORACUL scale - V. A. Brazhnik; L. O. Minushkina; A. O. Averkova; E. A. Zubova; N. R. Khasanov; A. S. Galyavich; M. A. Chichkova; E. D. Kosmacheva; D. A. Zateyshchikov (Кардиоваскулярная терапия и профилактика)
Aim. To compare the diagnostic value of different bleeding risk scales in patients with acute coronary syndrome (ACS).Material and methods. The study included 1502 patients with ACS from the observational, open-label, multicenter trial ORACUL II. The mean age was 65,7±12,9 years. At follow-up visits (hospital discharge, 25, 90, 180 and 360 days from the index event), all cases of bleeding were recorded with a description of bleeding characteristics, source, severity, treatment, and classification according to the BARC, TIMI, and ISTH scales.Results. During the follow-up period, bleeding was recorded in only 170 (11,3%) patients: within the index hospitalization — in 39 (2б6%), within a year after the index hospitalization — in 131 (8,6%). In 19 (1,2%) patients, recurrent bleeding at several visits was recorded. In comparison with such scores as CRUSADE, ACTION-ICU, ACUITY, PARIS, the ORACUL scale had the highest predictive value in relation to the in-hospital bleeding risk. The only scale with comparable diagnostic value was the BleeMACS score. It should be noted that the ORBIT and HASBLED scores had a lower predictive value for the in-hospital bleeding risk. In general, all scores were better at predicting major bleeding and slightly worse for clinically relevant ones.Conclusion. The ORACUL scale seems to be the most acceptable tool for assessing the bleeding risk in patients after ACS in actual clinical practice in Russia.